PENGARUH STRATEGI PROMOSI TERHADAP PENINGKATAN PENJUALAN PRODUK PADA UD. TAHU NIAS - Teodor Denius Halawa; Yupiter Mendrofa; Otanius Laia; Fakta Solala Zebua (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aims to determine whether there is a significant influence between product quality and customer loyalty at Toko Makmur Tani. The research method used in this study was quantitative research. The results of data analysis indicate that product quality has a positive and significant effect on customer loyalty. The regression coefficient value of 0.740 with a t-value of 6.022 and a significance level of 0.000 (<0.05) indicates that every increase in product quality will significantly increase customer loyalty. Based on the coefficient of determination (R Square) of 0.531, this means that product quality has a 53.1% effect on customer loyalty, while the remaining 46.9% is influenced by other factors not examined, such as price, service quality, brand image, and promotion.